2012
DOI: 10.1002/hon.2028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical heterogeneity of de novo 11q deletion chronic lymphocytic leukaemia: prognostic relevance of extent of 11q deleted nuclei inside leukemic clone

Abstract: Deletion on the long arm of chromosome 11 occurs in 5-20% of chronic lymphocytic leukaemia (CLL) patients. We analysed clinical-biological characteristics of 131 CLL patients carrying 11q deletion documented before therapy (de novo 11q deleted CLL). De novo 11q deleted CLL were characterized by high frequencies of unmutated immunoglobulin variable heavy genes, multiple fluorescence in situ hybridization aberrations and lymph node involvement. Factors significantly associated with shorter time to first treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
(46 reference statements)
6
16
1
1
Order By: Relevance
“…In contrast to 17p and 13q deletion groups, patients with 11q deletion did not exhibit a statistically significant association between TTFT and percentage of abnormal nuclei. Thus, we were unable to confirm an association between high percentage 11q deletion and adverse outcomes reported by Marasca et al (2013) and Jain et al (2015). Similarly, we were unable to confirm an association between small clones with TP53 mutation and poor survival (Rossi et al , 2014), assuming that small clones with TP53 mutation are comparable to our patients with FISH detectable but low percentages of 17p deletion.…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast to 17p and 13q deletion groups, patients with 11q deletion did not exhibit a statistically significant association between TTFT and percentage of abnormal nuclei. Thus, we were unable to confirm an association between high percentage 11q deletion and adverse outcomes reported by Marasca et al (2013) and Jain et al (2015). Similarly, we were unable to confirm an association between small clones with TP53 mutation and poor survival (Rossi et al , 2014), assuming that small clones with TP53 mutation are comparable to our patients with FISH detectable but low percentages of 17p deletion.…”
Section: Discussioncontrasting
confidence: 66%
“…Whilst it is optional to provide an estimation of the clone size for each separate abnormality reporting is encouraged where distinct sub clones are identified. This can be useful for follow up studies and may have clinical relevance in the future (Dal Bo et al, ; Marasca et al, ).…”
Section: Array Reportingmentioning
confidence: 99%
“…Alternative possibilities that have been considered include deletion, mutation or epigenetic silencing of other genes either within or outside the MDR or the associated genomic complexity. 8,[21][22][23] Neither candidate gene sequencing nor whole exome sequencing studies have identified mutations within other genes located in the MDR. 24,25 However, recent data have revealed a high incidence of deletion or, more rarely, mutation of BIRC3, a negative regulator of noncanonical NFκB signaling located at 11q22.…”
Section: Introductionmentioning
confidence: 99%